Perspectives on Teacher Promotion in Nepal: Voices from Stakeholders and English Teachers (Journal of Musikot Campus, 2025)
This study aims to investigate the provision of teacher promotion and explore how stakeholder and secondary level English teachers perceive it. I used narrative inquiry as a research design to collect and analyze the data. I used semi structured interview with five permanent English teachers, two participants from Education Development and Coordination Unit Dang, a participant from Ministry of Education Science and Technology, Singhdurbar and one participant from Teacher Service Commission, Bhaktapur. I transcribed the interview, coding and thematizing to draw the findings and conclusion. The findings of the study revealed that teacher promotion is necessary for quality education, motivation and teachers’ professional growth and development. The study also revealed that seniority has less impact on the teacher’ promotion as it is strongly depended on teacher’s performances including their academic degree. There are biases and technical errors so that a teacher cannot get their promotion for a long period of time. The quotas have not been added for long time affecting teachers’ promotion indirectly. It is hoped that this study will provide a better understanding of teacher promotion in general and in Nepal in particular.